2006
DOI: 10.1149/1.2336075
|View full text |Cite
|
Sign up to set email alerts
|

H[sub 2]S Poisoning of Solid Oxide Fuel Cells

Abstract: The influence of normalH2S fuel impurity on power generation characteristics of solid oxide fuel cells (SOFCs) has been analyzed by measuring cell voltage at a constant current density, as a function of normalH2S concentration, operational temperature, and fuel gas composition. Reversible cell voltage change was observed around 1000°C , while fatal irreversible degradation occurred at a lower operational temperature, at a higher normalH2S concentration, and at a lower fuel normalH2∕CO ratio. Sulfur to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
319
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(335 citation statements)
references
References 18 publications
15
319
1
Order By: Relevance
“…5,7 However, ScYSZ-Hi reported in our previous work 11 shows that Ni/ScYSZ-based cells can likewise be "pushed" into a longterm degradation regime at similar conditions (gas and temperature) through increased cell overpotential. Consequently, the long-term irreversible degradation for the sprayed Ni/YSZ-based cell, YSZ-Hi-Spr, originally reported by Hagen et al 5 compared to the more stable tape cast laminated and Sc-doped cell (ScYSZ-Low) was not merely a question of ScYSZ versus YSZ, although this difference in composition, together with microstructural differences, can play a role in the initial cell performance loss and the cell overpotential "threshold" at which the irreversible long-term degradation is initiated.…”
Section: High Overpotential H 2 S Test -Eis-mentioning
confidence: 94%
See 2 more Smart Citations
“…5,7 However, ScYSZ-Hi reported in our previous work 11 shows that Ni/ScYSZ-based cells can likewise be "pushed" into a longterm degradation regime at similar conditions (gas and temperature) through increased cell overpotential. Consequently, the long-term irreversible degradation for the sprayed Ni/YSZ-based cell, YSZ-Hi-Spr, originally reported by Hagen et al 5 compared to the more stable tape cast laminated and Sc-doped cell (ScYSZ-Low) was not merely a question of ScYSZ versus YSZ, although this difference in composition, together with microstructural differences, can play a role in the initial cell performance loss and the cell overpotential "threshold" at which the irreversible long-term degradation is initiated.…”
Section: High Overpotential H 2 S Test -Eis-mentioning
confidence: 94%
“…externally controlled conditions such as set temperature and fuel composition) one should not expect formation of nickel sulfide (Ni 3 S 2 ) either. 3,7,46,47 However, the given test conditions and values for pO 2-anode-compartment are "overall" numbers for the entire anode utilization volume and do not provide information on exact conditions on the nanometer scale of the anode at -or in the nano-scale vicinity of -the TPB at which the pO 2 , gas composition and temperature can be significantly different. Kishimoto and co-workers reported that the Ni-S system is complex and includes Ni-S eutectics between Ni and Ni 3 S 2 and showed thermodynamic data for the significant increase (∼ doubling) of the solubility of oxygen and sulfur in Ni when increasing the oxygen potential, pO 2 , by one order of magnitude.…”
Section: Post-mortem Analysis Of the Anode Layers-mentioning
confidence: 99%
See 1 more Smart Citation
“…It is already known that sulfur species adsorb onto the surface of Ni anode catalysts when H 2 S is mixed into fuels, 19,20 resulting in both electrode and internal reforming reactions being deactivated. As a result, oxygen ions passing through the electrolyte contribute to oxidation of the anode Ni, rather than the electrode reactions necessary for fuel cell operation.…”
Section: Degradation During the Shutdown Protocolmentioning
confidence: 99%
“…Although these reduction and oxidation mechanisms are not fully understood, it is generally accepted that the reactions follow different stages and involve more than one reaction path. Therefore, the reaction kinetics at the interphases strongly depends on chemical and structural properties of the cell components [6,[11][12][13], the electrode morphology (particle size, porosity, thickness, etc.) [14], the characteristics at the interfacial boundary [15,16] and other working parameters as the operation temperature and the gas partial pressure [17].…”
Section: The Role Of the Electrode/electrolyte Interphase In A Sofcmentioning
confidence: 99%